RESPONS PERTUMBUHAN DAN PRODUKSI DUA VARIETAS UBI JALAR TERHADAP PEMBERIAN BERBAGAI SUMBER KALIUM - Wendy V K Sembiring (Institute of Computer Science (IOCS), 2021)
The research was conducted at Tanjung Anom Subdistrict of Pancur Batu, Deli Serdang District of Medan, North Sumatera with an altitude of ± 25 meters above sea level from April until August 2017, using group randomized design with two factors, i.e : varieties (Beta 1 and Local Perbaungan) and sources of potassium (control, KCl, biochar, empty palm fruit bunch). The result showed that the treatment of two varieties had significant effect on tuber length parameters per sample, biomass weight per sample, tuber weight, and plant biomass weight, that the highest yield was obtained in Beta 1 treatment. The sources of potassium significantly affect all parameters of the study the interaction of the treatment of varieties and the provision of various types of potassium sources significantly affected all parameters, where the number of tubers and tuber weight per sample of treatment was highest in the treatment of Beta 1 varieties with KCl.